Additive manufacturing of an Fe–Cr–Co permanent magnet alloy with a novel approach of in-situ alloying. Issue 1 (31st December 2022) - Arneitz, S.; Buzolin, R.; Rivoirard, S.; Sommitsch, C.
Abstract: Additive manufacturing has become increasingly important in the production of magnetic materials in recent years due to the great demands for miniaturization and complex-shaped magnet parts. In this study, the laser beam-powder bed fusion process (LPBF) has been used to develop an in-situ alloying process for the additive manufacturing of a permanent magnet material of the Fe–Cr–Co system. This novel method allows for the production of complex alloys with a chemical composition suited to each specific case of application, achieved by using elemental powders or simpler commercial alloy powders as base materials. The core focus of this study has been on the development and characterization of the printing process using a Fe-30.5Cr-15Co-1.5Mo alloy. The in-situ alloying process has been developed by performing melt pool tests on the two main component powders Fe and Cr and by conducting parameter studies using two different powder mixtures with different sphericity of their components. The influence of different printing parameters and post-printing treatments on the chemical homogeneity and magnetic properties has been studied for selected samples. In addition, magnetic measurements at different temperatures have been performed to investigate the temperature stability of the magnetic properties of the 3D printed material. Impact Statement As by today, the current amount of research done on the additive manufacturing of magnetic materials is rather low. Most of research is focused on rare- earth containing magnetic materials. In this work therefore, we are taking another direction in which we will show that LPBF combined with in- situ alloying is an ideal method for the production of a great variety of different rare- earth free magnetic materials. The positive results of our work can both have an influence on the the scientific community, as further research in the field on different promising rare- earth free magnetic materials is to be expected. Furthermore, a positiv economic impact may occur since the production of rare- earth free magnetic materials is dependent on different raw material sources which are both more cost- effectiv and less critical in terms of their supply chain. This effect is also accompanied by a positive environmental impact, since the mining of rare- earth metals usually comes with considerable environmental pollution.